Guyton and Hall Textbook of Medical Physiology - Hall, John E.; Hall, Michael E. (Philadelphia, PA : Elsevier, 2021)
The world's foremost physiology textbook. Known for its clear presentation style, single-author voice, and focus on content most relevant to clinical and pre-clinical students, Guyton and Hall Textbook of Medical Physiology, 14th Edition, employs a distinctive format to ensure maximum learning and retention of complex concepts. A larger font size emphasizes core information while supporting information, including clinical examples are detailed in smaller font and highlighted in pale lavender - making it easy to quickly skim the essential text or pursue more in-depth study. This two-tone approach, along with other outstanding features makes this bestselling text a favorite of students worldwide. Key features include : offers a clinically oriented perspective written with the clinical and pre-clinical student in mind, bridging basic physiology with pathophysiology ; focuses on core material and how the body maintains homeostasis to remain healthy, emphasizing the important principles that will aid in later clinical decision making ; presents information in short chapters using a concise, readable voice that facilitates learning and retention ; contains more than 1,200 full-color drawings and diagrams - all carefully crafted to make physiology easier to understand ; features expanded clinical coverage including obesity, metabolic and cardiovascular disorders, Alzheimer's disease, and other degenerative diseases.--adapted from back cover.
Unit I. Introduction to Physiology : The Cell and General Physiology -- Unit II. Membrane Physiology, Nerve, and Muscle -- Unit III. The Heart -- Unit IV. The Circulation -- Unit V. The Body Fluids and Kidneys -- Unit VI. Blood Cells, Immunity, and Blood Coagulation -- Unit VII. Respiration -- Unit VIII. Aviation, Space, and Deep-Sea Diving Physiology -- Unit IX. The Nervous System : A. General Principles and Sensory Physiology -- Unit X. The Nervous System : B. The Special Senses -- Unit XI. The Nervous System : C. Motor and Integrative Neurophysiology -- Unit XII. Gastrointestinal Physiology -- Unit XIII. Metabolism and Temperature Regulation -- Unit XIV. Endocrinology and Reproduction -- Unit XV. Sports Physiology.
Revised edition of: Guyton and Hall textbook of medical physiology / John E. Hall, PhD, Arthur C. Guyton Professor and Chair, Department of Physiology and Biophysics, Director, Mississippi Center for Obesity Research, University of Mississippi Medical Center, Jackson, Mississippi. 13th edition. [2016].
Includes bibliographical references and index.
Keywords: Physiological Phenomena